Efektifitas Manajemen Pengelolaan Dana Zakat dalam Meningkatkan Kesejahteraan Mustahik di Badan Amil Zakat Nasional (Baznas) Pusat - Windy Fuji Astuti; Naufal Kurniawan (Jurnal Ekonomi & Bisnis, 2023)
Indonesia has the potential for zakat as a tool to reduce and improve poverty and people's welfare. The management of zakat funds certainly has a very vital role in the success of achieving the benefit of the people. This study evaluates the effectiveness of the management of the optimal distribution of zakat funds so that it can significantly contribute to poverty reduction and better welfare. This type of research is library research conducted using existing literature on Central Baznas, Jakarta year 2011- 2021 by collecting data through a literature review of books, notes, and research reports from previous studies. Data analysis techniques were carried out using inductive techniques consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate: Baznas Pusat Jakarta has been effective in managing zakat management, both in planning, organizing, implementing and supervising.